World Economic Outlook, October 2019 : Global Manufacturing Downturn, Rising Trade Barriers. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2019)
Global growth is forecast at 3.0 percent for 2019, its lowest level since 2008-09 and a 0.3 percentage point downgrade from the April 2019 World Economic Outlook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet